WORKLOAD ANALYSIS USING WORK SAMPLING AND NASA-TLX FOR EMPLOYEE OF PRIVATE UNIVERSITY IN SURABAYA - Widiasih, Wiwin; Nuha, Hilyatun (Jurnal Ilmiah Teknik Industri, 2019)
Employees are valuable asset in an organization. The organization can be defined as two types namely a profit or nonprofit company, and government institution. Employees as a capital human for these organization have big roles for performance measurement. Performance measurement of employee is used to determine whether the worker has been working efficient or not. Workload analysis is defined as analysis of a set or number of activities that must be completed by an organizational unit or position holder within a certain period of time. In this research, it will show employee workload analysis using two approaches in order to complete each other. Firstly, work sampling method was used to determine workload in physically. Secondly, NASA-TLX was utilized to analyze workload in mentally. Pareto method will also take a part for analysis the research result to be more comprehensive. This research has conducted in an East Java?s University-Indonesia. The respondents are employees who have each job description to do their work in each position. The employee?s workload will be calculated both physical and mental. From 25 position observed, show the job position who has strategic characteristic mostly have very high mental workload whereas the job position who has operational characteristic mostly have high physical workload